Unspoken obligations: perspectives on post-trial responsibilities from Tanzanian research ethics committee and researchers - Rose Mwangi; Sabina Mtweve; Blandina T. Mmbaga; Rachel Manongi (Global Bioethics)
Introduction: Ethical considerations in clinical research extend beyond trial completion, emphasizing post-trial responsibilities to ensure participant well-being, particularly in resource-limited settings. This study explores the perspectives of researchers and Research Ethics Committee (REC) members in Tanzania regarding post-trial obligations and their alignment with key ethical frameworks such as the Belmont Report, CIOMS guidelines, and the Declaration of Helsinki. Methods: A qualitative phenomenographic case study was conducted, including a focus group discussion with 11 REC members from three Good Samaritan Foundation (GSF) institutions with a longstanding research collaboration with international partners world wide. Additionally, in-depth interviews were conducted with purposively selected researchers. Data saturation guided the sample size, and NVIVO 12 software facilitated thematic analysis. Results: Findings revealed significant gaps in post-trial care, particularly in maintaining access to interventions. RECs and researchers face challenges in fulfilling post-trial responsibilities calling for clear guidelines and sustainable post-trial mechanisms in resource poor settings. A disconnect exists between RECs’ ethical oversight and researchers’ practical realities. Community engagement is crucial for ethical research but is often inadequately sustained. Conclusion: Ethical frameworks must explicitly address post-trial obligations, particularly in low-resource settings. Strengthening communication between RECs, researchers, and sponsors, along with ongoing community engagement, is vital for equitable and sustainable global health research.